The Social Framework for Projects: a conceptual but practical model to assist in assessing, planning and managing the social impacts of projects. Issue 1 (2nd January 2017) - Smyth, Eddie; Vanclay, Frank
Abstract: The Social Framework for Projects assists in understanding, assessing, planning and managing the social issues associated with big projects, such as those leading to the resettlement or displacement of people. The Framework was iteratively developed by assessing existing models (e.g. Sustainable Livelihoods Approach of the UK Department for International Development; the Impoverishment Risks and Reconstruction model of Michael Cernea; the Capability Approach of Amartya Sen; Asset Based Community Development and other capitals-based approaches), reflecting on our practical experience in large projects, and on the basis of input and feedback from a wide range of stakeholders. It was designed to be compatible with the International Finance Corporation's environmental and social performance standards and international best practice. It consists of 8 key social and environmental categories which address all the issues that contribute to people's well-being and the social sustainability of projects, namely: people's capacities, abilities and freedoms to achieve their goals; community/social supports and political context; livelihood assets and activities; culture and religion; infrastructure and services; housing and business structures; land and natural resources; and the living environment. The Framework is a conceptual model, a practical methodology and a communications tool to ensure that the process of mitigating negative social impacts and enhancing the benefits of large projects is effective and accessible to all stakeholders.